Successful living-donor liver transplantation for sustained liver failure even after resolution of infiltrative massive hepatic invasion of stage 4S neuroblastoma: a case report - Kanta Jobara; Ayako Yamamori; Masato Shizuku; Nobuhiko Kurata; Yasuhiro Fujimoto; Hideki Muramatsu; Yoshiyuki Takahashi; Yasuhiro Ogura (Surgical Case Reports)
Abstract Background Neuroblastoma is the most common extracranial solid tumor in childhood. Stage 4S neuroblastoma is a unique subset of neuroblastoma characterized by a favorable course and potentially low malignancy with a high rate of spontaneous tumor regression. However, recent reports have shown that there is a subgroup of patients with stage 4S neuroblastoma characterized by MYCN amplification, chromosomal aberrations, age of < 2 months at diagnosis, and significantly poorer outcomes. Case presentation A 1-month-old male infant with a huge abdominal tumor was transferred to our hospital and diagnosed with stage 4S neuroblastoma. The patient showed respiratory distress due to abdominal compartment syndrome secondary to massive hepatic invasion, and he required a silo operation and mechanical ventilation. After chemotherapy using carboplatin and etoposide, the infiltrative massive hepatic invasion was resolved and the abdominal compartment syndrome gradually improved; however, liver dysfunction as evidenced by hyperbilirubinemia, coagulopathy, and hyperammonemia continued. At the age of 3 months, living-donor liver transplantation was performed for treatment of sustained liver failure using a reduced lateral segment graft from the patient’s father. Post-transplant liver function recovered immediately. Examination of the explanted liver demonstrated that the majority of liver tissue had been replaced by fibroblastic cells after massive hepatocyte dropout. There were only small areas of residual neuroblastoma cells in the liver specimen. The patient was discharged from the hospital 5 months after transplantation with home intermittent respiratory support. At the time of this writing (23 months after liver transplantation), he was in good condition with no signs of recurrence of neuroblastoma. Conclusions We have herein presented a case of successful pediatric living-donor liver transplantation for sustained liver failure even after resolution of infiltrative massive hepatic invasion of stage 4S neuroblastoma. Our case clearly shows that liver transplantation can be added as an appropriate extended treatment option for liver failure after resolution of stage 4S neuroblastoma.